2020
DOI: 10.2174/1874210602014010172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Dimorphism with Mandibular Parameters by Digital Panoramic Radiography

Abstract: Introduction: Sex determination is the first step of personal identification in the field of forensics and is essential for reconstructive profiling. The skull appears to be the most reliable part of the skeleton, apart from the pelvis, in sex determination. Tooth and bone are used as a key tool for personal identification due to their high resistance to decomposition and degradation. The present study aimed to evaluate the sexual dimorphism with mandibular parameters by digital panoramic radiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 23 publications
(30 reference statements)
6
12
1
Order By: Relevance
“…All the variables showed significant differences between the sexes (p < 0.001), except for the angular variables (Agn-go_D, Agn-go_E) with p-values > 0.05. P-values < 0.001 agree with comparable studies: Sairam et al (2016) referred p-values < 0.001, Farzaneh et al [1] p < 0.0001, Abu-Taleb et al [10] p < 0.001, Damera et al [4] p = 0.00, Indira et al [3] p < 0.001, Sambhana et al [11] p < 0.0001, and Al-Shamout et al [13] p < 0.0001. However, for angular measurements with p-values > 0.05, some comparable studies reported different results: Farzaneh et al [1] p < 0.0001, Abu-Taleb et al [10] p < 0.001, Da mera et al [4] p = 0.00, and Chole et al [12] p < 0.05.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…All the variables showed significant differences between the sexes (p < 0.001), except for the angular variables (Agn-go_D, Agn-go_E) with p-values > 0.05. P-values < 0.001 agree with comparable studies: Sairam et al (2016) referred p-values < 0.001, Farzaneh et al [1] p < 0.0001, Abu-Taleb et al [10] p < 0.001, Damera et al [4] p = 0.00, Indira et al [3] p < 0.001, Sambhana et al [11] p < 0.0001, and Al-Shamout et al [13] p < 0.0001. However, for angular measurements with p-values > 0.05, some comparable studies reported different results: Farzaneh et al [1] p < 0.0001, Abu-Taleb et al [10] p < 0.001, Da mera et al [4] p = 0.00, and Chole et al [12] p < 0.05.…”
Section: Discussionsupporting
confidence: 89%
“…The CCI values obtained from the comparison of measurement times for 11 variables were above 0.75, indicating excellent reproducibility, and in 3 variables, the CCI values were slightly below 0.75, defining reproducibility as good [8]. These results are in line with similar literature: Farzaneh et al [1] reported 0.92 for intra-observer reproducibility, and Damera et al [4] a value of 0.81 [1,4].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[4][5][6] In cases where there is no intact skull bone, the mandible plays an important role because it is part of the skull bone, the most dimorphic, the largest, and the strongest. [4][5][6][7][8] In the mandible, the condyle and ramus are the two areas that show the highest sexual dimorphism. 3 One of the variables that shows sexual dimorphism in the mandible is through the interprocessus.…”
mentioning
confidence: 99%
“…10 The lower cost and wide area coverage and ease of preparation make panoramic radiographs the best choice. 8 Based on existing studies, the accuracy of panoramic radiographs in the anatomical measurement of the mandible has been demonstrated and shows that the mandible has a high sexual dimorphism. 2 Research to measure the distance between interprocessus has never been done before, therefore it is important to do this research.…”
mentioning
confidence: 99%